Reconstructing the Tunic from Lendbreen in Norway - Vedeler, Marianne; Hammarlund, Lena (Archaeological Textiles Review, 2017)
A woven wool tunic with damaged sleeves and repairs to the body dating from AD 230 to AD 390 was discovered on the Lendbreen glacier in Oppland County, Norway in 2011. The Norwegian Mountain Centre in Lom (Norsk Fjellsenter) and the Museum of Cultural History at the University of Oslo each commissioned a reconstruction of the tunic for exhibition and research into prehistoric textile production. The original was woven in 2/2 diamond twill with differently coloured yarns producing a deliberate and even mottled effect. The reconstruction project investigated the materials required, the likely tools used and the weave, with new investigations into the processes of collecting, sorting, and spinning the wool, the thread system, the finishing treatment and sewing to produce two tunics as they might have been as new with complete sleeves and no repairs. Estimates for the labour required for each stage suggested a total of just over 402 hours per tunic.